Antibacterial properties of glycosylated surfaces: variation of the glucosidal moiety and fatty acid conformation of grafted microbial glycolipids - Valotteau, Claire; Roelants, Sophie L. K. V.; Dhasaiyan, Prabhu; Zibek, Susanne; Guenther, Michael; Soetaert, Wim; Everaert, Bernd; Pradier, Claire-Marie; Babonneau, Florence; Baccile, Niki; Humblot, Vincent (Molecular Systems Design & Engineering, 2020)
Glycosylated surfaces can display antimicrobial properties. It has been shown that sophorolipids can be used to develop biocidal coatings against Gram-positive and Gram-negative bacteria, but with a limited efficiency so far. Therefore, it appears necessary to further investigate the surface antibacterial activity of a broader set of structurally related glycolipids. The present work explores the influence of the glucosidic moiety (gluco-, sophoro-, cellobio-) and the fatty acid backbone (saturated,cisortransmonounsaturated). We show that the fatty acid backbone plays an important role:cisderivative of sophorolipids (SL) grafted onto model gold surfaces has better biocidal properties than saturated (SL0) andtransmonounsaturated (SLt) molecules, which appear to be inefficient. The number of glucose units is also a key factor: a one-third decrease in antibacterial activity is observed when having one glucose unit (GL) compared to two (SL). Sugar acetylation (SLa) does not seem to have an impact on the biocidal properties of surfaces. These results are not limited to sophorolipids, with cellobioselipids (CL) leading to similar antibacterial observations.